1996
DOI: 10.1007/bf00199508
|View full text |Cite
|
Sign up to set email alerts
|

Antigastric autoantibodies in Helicobacter pylori gastritis: prevalence, in-situ binding sites and clues for clinical relevance

Abstract: Colonization of human gastric mucosa with Helicobacter pylori leads to chronic active gastritis and induces the occurrence of an acquired mucosa-associated lymphoid tissue (MALT) in the stomach. This remodelling of the gastric mucosa together with chronic antigen persistence may induce autoimmune reactions. The aim of this study was to investigate humoral autoimmune reactions to human gastric mucosa in H. pylori gastritis and their clinical relevance. Sera from patients with dyspeptic symptoms were tested for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
53
1
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 17 publications
6
53
1
1
Order By: Relevance
“…However, conflicting results have also been reported (24,29). Simultaneous occurrence of H. pylori infection and autoimmune reaction observed in previous investigations (5)(6)(7)(8) or our study population cannot be interpreted to support a causal relationship between bacterial infection and autoimmune response. Because of the crosssectional study design with simultaneous ascertainment of infection, autoimmune response and CAG, temporal relationships between occurrence of bacterial infection, autoimmune response and development of CAG as well as potential disease-related loss of H. pylori infection could not be observed.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…However, conflicting results have also been reported (24,29). Simultaneous occurrence of H. pylori infection and autoimmune reaction observed in previous investigations (5)(6)(7)(8) or our study population cannot be interpreted to support a causal relationship between bacterial infection and autoimmune response. Because of the crosssectional study design with simultaneous ascertainment of infection, autoimmune response and CAG, temporal relationships between occurrence of bacterial infection, autoimmune response and development of CAG as well as potential disease-related loss of H. pylori infection could not be observed.…”
Section: Discussioncontrasting
confidence: 84%
“…3,4). Following the discovery of Helicobacter pylori (H. pylori) and the establishment of a causal relationship between H. pylori infection and CAG (1,2), several studies have reported that a considerable number of patients with H. pylori infection also expressed autoantibodies against Hþ/Kþ-ATPase (5)(6)(7)(8). The presence of these autoantibodies in H. pylori infection was also significantly associated with higher fasting serum gastrin levels, a lower pepsinogen I to II ratio, and reduced secretion of gastric acid (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Parietal cell autoantibodies have been correlated with the occurance of atrophic gastritis in H. pylori infected humans (21,22). To screen for autoantibodies, sera from infected transgenic and normal mice were incubated with sections prepared (Fig.…”
Section: Lementioning
confidence: 99%
“…32 In addition to the cellular immune response, the humoral response to H. pylori may contribute to disease pathogenesis. 14,15,43 Approximately 89% of H. pylori-infected humans develop anti-Helicobacter antibodies that cross-react with the gastric mucosa, 41 and 25% of these individuals develop antibodies that bind to the canaliculi of parietal cells. 6 These autoantibodies have been correlated with the presence and degree of inflammation and with atrophy of the gastric glands.…”
mentioning
confidence: 99%
“…43 Specifically, the binding of antibodies to parietal cell canaliculi was significantly correlated with H. pylori infection, the presence of fundic (and not antral) gastritis, increased numbers of periglandular and IELs, increased destruction of the fundic glands, and gastric atrophy. [14][15][16]42,43,51 This histologic pattern is most similar to that commonly seen in captive cheetahs, so it is possible that affected cheetahs may also develop Helicobacter antibodies that cross-react with the gastric epithelium.…”
mentioning
confidence: 99%